Mikroudgravning: En metode til dokumentation af en mikrostratigrafi - Strehle, Helle (Kuml, 2025)
Micro-excavation A method for documenting a micro-stratigraphy This article describes a method for harvesting, recording and systemising data from a heavily degraded and compressed body of block-lifted archaeological remains. The thickness of these remains was a maximum 3 cm, and identification was only possible with the aid of a microscope. An unorthodox way of implementing Harris matrices is demonstrated, by which the archaeological remains can reveal a picture of a more than 3000-year-old burial ritual. The article first describes the archaeological context of the Kongsted burial mound, the latest of the iconic Danish Bronze Age mounds containing well-preserved oak-log coffins to be investigated, and the first since 1935. Figure 1 shows how the block was lifted within the oak-log coffin and figure 3 combines the geo-referenced sword with the skeletal parts. In figure 2, the sword is seen exposed in the block in the conservation laboratory. The article describes in detail the special conditions for the preservation of organic materials prevailing in a Bronze Age burial mound with a preserved iron pan. For example, for protein-based materials such as hair (fig. 7), fur (fig. 6), woollen textile fibres (fig. 12), skin fibres (fig. 8) and the seldom surviving horn, which constitutes the hilt of the sword (fig. 14). It is then explained how the corroding bronze sword has created special preservative conditions for organic materials such as the mineralised hair from fur (fig. 9). Furthermore, the article describes how the organic remains were extracted from the block and how they were identified under the microscope and with reference to the relevant literature. Features that are characteristic of bone (fig. 10) and skin (fig. 8) were detected at x100 magnification and hair at x200 magnification (fig. 7). Archaeologically interesting details were also identified, such as the preserved oak sheath for the sword (fig. 15) and even its fur lining (fig. 16). Textile made a coarse, plainly woven z-spun type woollen thread was detected as being widespread in the vicinity of the sword (figs. 11-12), while a construction detail of the cloth, a curved edge, was also visible (fig. 13). The block was defined by macroscopically obvious remains, namely the lid and bottom of the coffin, the skeletal parts and the bronze sword. The heavily degraded, compact fill was preserved between these clear horizons. Multiple samples were taken from the fill, the materials identified and their relation to each other noted on several plan drawings of the various horizons. The material identifications were illustrated by short Harris matrices, which were then combined with the horizons of the block to form a ‘cloud of matrices’, indicating the overall micro-stratigraphy of the contents of the grave (fig. 4). Tentative suggestions about the nature of the burial ritual are made and illustrated (fig. 5). Finally, the potential for employing this method for harvesting and recording data from a degraded micro-stratigraphy is outlined.